Análise do conforto térmico de uma edificação de ensino superior em Campina Grande – PB - Souza, Aderson Rodrigues de (2017)
The importance of thermal comfort studies in educational buildings is associated with the relationship that this condition has with the performance of human activities, providing a thermally comfortable environment better levels of concentration and attention. Thus, the objective of this research is to evaluate the thermal comfort conditions of classrooms and administrative rooms, naturally ventilated, in a building of higher education, in the city of Campina Grande, Northeast Region of Brazil, where the weather is predominantly hot and humid. In order to obtain the results, two methods traditionally used in this type of research were applied. The analytical method, included in International Standards ISO 7730 (2005) and ASHRAE 55 (2010), provides results on 4 environmental and 2 personal variables, collected from the studied environments. The second method consists in the application of questionnaires to the ordinary users of the environments aiming to obtain personal answers about the real thermal sensations. The analysis of the results showed that the comfort zones, verified in the building, were distinct for each season of the year in which the research was developed. By personal votes, the comfort temperature ranges in the fall were broader than those provided by the technical standards. However, in the winter, the normalized method overestimated the ranges of comfort temperatures obtained by direct votes. The results of the thermal comfort zones were compared with those of other studies done in regions with climatological features similar to those of this work, as well as with those obtained in regions of colder climates, verifying the coherence between the data. This research concluded that, in the autumn season, the environments of the building provided its occupants with thermal discomfort for the heat most of the time, however, in the winter season, thermal comfort situations were predominant.